Extracting the dependence of directed flow differences on conserved charges - Lin Zi-Wei; Nayak Kishora; Shi Shusu (EPJ Web of Conferences)
Recently, seven produced hadron species have been used to construct multiple hadron sets with given differences in the net electric charge (∆q) and strangeness (∆S) between the two sides. A nonzero directed flow difference △v1 has been proposed as a consequence of the electromagnetic field produced in relativistic heavy ion collisions. Previously, we have shown with quark coalescence that Av1 and the slope difference △v′1 depend linearly on both △q and ∆S with zero intercept. Here we emphasize that a two-dimensional function or fit is necessary for extracting the △q- and △S-dependences of △v1. On the other hand, a one-dimensional fit gives a different value for the slope parameter of the ∆q- or ∆S-dependence. Furthermore, a one-dimensional fit is incorrect because its slope parameter depends on the arbitrary scaling factor of a hadron set and is thus ill-defined. We use test data of △v1 to explicitly demonstrate these points.